Effect of Ozone Exposure on Cardiovascular and Cerebrovascular Disease Mortality in the Elderly - Tianyun Wang; Junlong Wang; Li Sun; Ye Deng; Yuting Xiang; Yuting Wang; Jiamei Chen; Wen Peng; Yuanyao Cui; Miao He (Toxics, 2025)
Background: Ozone pollution has increased alongside China’s economic development, contributing to public health issues such as cardiovascular and cerebrovascular diseases. At present, the problem of an aging population is aggravated, which is worth more attention in terms of the health problems of elderly people. Methods: This study employed a distributional lag nonlinear model (DLNM) with Poisson regression to analyze the impact of ozone on cardiovascular and cerebrovascular disease mortality among the elderly in Shenyang, China, from 2014 to 2018. In addition, a time-series generalized additive regression model (GAM) was used to analyze the joint effect between PM2.5 and ozone. Results: We found a positive correlation between ozone and mortality from cardiovascular and cerebrovascular diseases in the elderly. The maximum relative risk (RR) of mortality from cardiovascular and cerebrovascular diseases for every 10 μg/m3 increase in ozone was 1.005 (95% CI: 1.002–1.008). Males (RR: 1.018, 95% CI: 1.007–1.030), individuals in unconventional marital status (RR: 1.024, 95% CI: 1.011–1.038), and outdoor workers (RR: 1.017, 95% CI: 1.002–1.031) were more vulnerable to ozone pollution. This study did not find significant differences in the impact of ozone pollution on cardiovascular and cerebrovascular disease mortality risks among different educational groups. Additionally, a joint effect between ozone and PM2.5 was observed. Conclusion: This study confirms that ozone exposure is positively associated with increased mortality from cardiovascular and cerebrovascular diseases. It emphasizes the joint effect of ozone and PM2.5 in exacerbating cardiovascular and cerebrovascular disease mortality.